Mitochondrial functionality and metabolism in T cells from progressive multiple sclerosis patients. Issue 12 (16th August 2019) - De Biasi, Sara; Simone, Anna Maria; Bianchini, Elena; Lo Tartaro, Domenico; Pecorini, Simone; Nasi, Milena; Patergnani, Simone; Carnevale, Gianluca; Gibellini, Lara; Ferraro, Diana; Vitetta, Francesca; Pinton, Paolo; et al.
Abstract: Patients with primary progressive (PP) and secondary progressive (SP) forms of multiple sclerosis (MS) exhibit a sustained increase in the number of Th1, T cytotoxic type‐1 and Th17 cells in peripheral blood, suggesting that the progressive phase is characterized by a permanent peripheral immune activation. As T cell functionality and activation are strictly connected to their metabolic profile, we investigated the mitochondrial functionality and metabolic changes of T cell subpopulations in a cohort of progressive MS patients. T cells from progressive patients were characterized by low proliferation and increase of terminally differentiated/exhausted cells. T cells from PP patients showed lower Oxygen Consumption Rate and Extracellular Acidification Rate, lower mitochondrial mass, membrane potential and respiration than those of SP patients, a downregulation of transcription factors supporting respiration and higher tendency to shift towards glycolysis upon stimulation. Furthermore, PP effector memory T cells were characterized by higher Glucose transporter ‐1 levels and a higher expression of glycolytic‐supporting genes if compared to SP patients. Overall, our data suggest that profound differences exist in the phenotypic and metabolic features of T cells from PP and SP patients, even though the two clinical phenotypes are considered part of the same disease spectrum. Abstract : Although primary progressive (PP) and secondary progressive (SP) multiple sclerosis are part of the same disease spectrum, their CD4+ T cells present profound metabolic differences T cells from PP show dysfunctional mitochondria and higher tendency to use glycolysis, while mitochondria from SP patients have fully functional mitochondria used for respiration.